Evaluation of bone mineral density in chronic glue sniffers - Dündaröz, M. Ruşen; Sarıcı, S. Ümit; Türkbay, Tümer; Baykal, Barboros; Kocaoğlu, Murat; Aydın, H. İbrahim and Gökçay, Erdal (The Turkish Journal of Pediatrics, 2002)
Although acute and chronic toxic effects of inhalant (glue) abuse have been well demonstrated on many organ systems, the effects on the skeletal system and bone mineral content of young people with this addiction have, to our knowledge, not yet been investigated by bone mineral density measurement. In the present study bone mineral density was measured by the dual-energy X-ray absorptiometry method in 25 children and adolescents with inhalant abuse and compared with that of a control group (n=30) to detect whether there was any delay in bone development or any decrease in bone mass. Chronological age, height and weight, serum calcium, phosphorus and alkaline phosphatase levels of the study group were not significantly different from those of the control group (p>0.05), whereas bone mineral density was significantly reduced in the study group (p=0.001). Teenagers with glue vapor abuse may carry an increased risk of future fracture even though the exact mechanism(s) responsible for the toxicity of glue vapor on bone metabolism remains to be determined. To ascertain the exact component of glue responsible for bone demineralisation may be of value in proposing a change in the composition of the glue. Education and/or rehabilitation programs currently have the greatest importance in preventing and overcoming the harmful effects of this public health problem which is so common in young children and adolescents.